A software development for investment analysis of LED lighting production project using fuzzy logic technique - Pullteap, Saroj; Samartkit, Piyawat; Kheovichai, Kanit; Seat, Han Cheng (Science, Engineering and Health Studies, 2020)
In this work, an application software for investment decision-making has been developed to analyze the feasibility level of an LED lighting production project. Particularly, the initial, manufacturing, administration, and financial expenses of the project, along with sales income and corporate tax, are applied as financial data. These inputs are then calculated into the net present value (NPV), internal rate of return (IRR), benefit-cost ratio (BCR), and discounted payback period (DPB) values, and further synthesized into the investment feasibility level using fuzzy logic. Additionally, the software allows flexible discount rate variation throughout project duration. The analysis results of 5 years duration project show that the NPV, IRR, BCR, and DPB were 6,307,759.46 Thai Baht, 24.04%, 1.08, and 3.38 years, respectively. Moreover, with 20% of expected profit margin, the feasibility level of project applying the floating discount rate of 7.12%-8.00% was “medium” at 77.89%, while project with fixed 8.00% rate suggested the level of “medium” at 67.34%. The discount rate variation, further, implied that using the floating discount rate was more attractive for the investment. Sensitivity analysis also revealed that the project was attractive until its income was 3.1% lower and expense was 2.4% higher than original. Therefore, the developed software could be suitable tool for more realistic project feasibility assessment and investment decision-making.